Les paradis fiscaux dans la mondialisation boursière - Maude Sainteville (L'Espace Politique)
Within the framework of global financial integration, cross-border listings enable firms to raise capital and to list their shares on foreign markets. Despite both the deregulation of financial markets and the widespread illusion of a so-called « global marketplace » spread by an intensive use of IT, corporate issuers are not indifferent to the location of their listing place(s). On the contrary, they manoeuvre astutely in order to benefit at best from the resources, networks and opportunities provided by the different places throughout the financial world. Firms not only select markets meticulously to list their shares, but some of them raise capital and quote their equities on major markets through their subsidiaries, dummy entities or legal headquarters incorporated within tax havens as well. Tax havens thus fit into the worldwide networks of cross-listings.Which actors and powers use and benefit from tax havens?  Based on the study of the worldwide matrices of cross-listings -- built thanks to a data compilation of the stock markets' listings in 2007 -- this article proposes to lift the veil on the listing strategies of transnational firms and to observe the position of tax havens in the networks of the global integration of financial markets by replying to the question:  what are the relational preferences within the group firms-states-listing places?